Standardized Follow-up Plan For Depression Through The Implementation Of Provider Note And Nurse Follow-up Phone Call Templates - Farrah Lee Rosentreader (Journal Of Nursing Practice, 2021)
Background: Depression is highly prevalent in primary care settings and depressed patients of all ages are seen by their Primary Care Provider (PCP) for treatment (Datto et al., 2003).  In order to adequately treat depression, PCPs must follow the clinical guidelines for follow-up.Purpose: The purpose of this project was to implement a standardized follow-up plan for patients aged 12 and older with a positive screen for depression using the Patient Health Questionnaire (PHQ-9) screening tool.Methods: The setting was a rural clinic in Broken Bow, Nebraska.  The sample included 89 patients seen between September 1 -November 30, 2020 who met the criteria of a PHQ-9 score of 5 or greater compared with 47 patients seen between September 1 -November 30, 2019. Quantitative data was analyzed using descriptive statistics, frequency and means and compared between before and after implementation of this quality improvement project.Results: In 2019, 11.3 % of patients reported depression. That more than doubled to 25.6 % in 2020.  Of the depressed patients in 2019, 36.2% had mild depression, while the number almost doubled to 60.7% in 2020. The 2020 PHQ-9 results were reviewed from most severe down to mild depression.  Of the 35 patients with the highest severity, 89% had at least one measure completed representing an adequate follow-up plan.  Referral rates improved from 12.8% in 2019 to 14.6% in 2020.  Medication was the most common treatment in both years with 57.4% in 2019 and 27% in 2020.  Completed follow-ups improved from 45.5% in 2019 to 73% in 2020; with 1 nurse phone call follow-up and one CSSR-S completed.Conclusion: It is unknow the affects from the 2020 pandemic.  However, and increase in mild depression shows a need to know how to treat sub-threshold depression. The use of the template as a guide led to improvement on all measures. However, some measures were used only sparingly and use may be improved with increased acceptance of the guide.